Climate Change Induced Occupational Shifts of Fishermen in Selected Coastal Areas of Central Kerala: Fishermen Perspective - Kanjirakkattu, Anju Alex; V. P. Ancy; A. V. Shibu (Fishery Technology, 2023)
Traditional coastal fisher-folks are highly vulnerable to climate change as they face limitations on occupational flexibility, leading to economic constraints. The distribution and availability of coastal fishery resources, which determine the livelihood of the traditional fisher-folks, are being influenced by factors such as sea surface temperature, salinity, wind patterns, tide levels, coastal erosion, etc. Climate induced variations influence distribution of fish and catch per unit effort, which necessitate modification in fishing strategies and adaptation practices. The goal of the current study was to rank the weather-related parameters influencing the occupational shifts of traditional fishermen in the coastal state of Kerala’s three fishing villages of Thrikkunnapuzha, Chellanam, and Elamkunnapuzha in terms of fishermen’s perspective. Additionally, the study tries to evaluate the various occupational transitions. The methodology involved extensive field visits and interactions with fishers, fishermen groups, local organizations, self-help groups and non-government organizations. Rising sea surface temperature, among other weather-related characteristics, was the main contributor to the change in occupation, according to fishermen. Additionally, it was noted that 41 % of respondents said that fisherfolks of study area opted for alternative jobs and changed their operational area to combat the climate change risks. To develop effective adaptation measures, the complex interaction of social, economic, and environmental systems must be studied and community-oriented adaptation strategies should be developed along the coast. For the mitigation of climate related uncertainties, the local community and public institutions should implement reactive or anticipatory action plans.